Rin-Ne. Volume 1 - Takahashi, Rumiko, 1957- (Viz Media, 2009)
"Sakura's curiosity about the mysterious Rinne draws her deeper into an amazing world on the boundary between the living and the dead. Helping Rinne is one thing, but will tagging along with him leave her trapped in the afterlife? And does Rinne really know what he's doing? Dealing with the afterlife isn't easy, especially when you don't know all the rules!"--P. [4] of cover.